Oncostatin M induces hyperalgesic priming and amplifies signaling of cAMP to ERK by RapGEF2 and PKA. Issue 6 (20th September 2020) - Garza Carbajal, Anibal; Ebersberger, Andrea; Thiel, Alina; Ferrari, Luiz; Acuna, Jeremy; Brosig, Stephanie; Isensee, Joerg; Moeller, Katharina; Siobal, Maike; Rose‐John, Stefan; Levine, Jon; Schaible, Hans‐Georg; et al.
Abstract: Hyperalgesic priming is characterized by enhanced nociceptor sensitization by pronociceptive mediators, prototypically PGE2 . Priming has gained interest as a mechanism underlying the transition to chronic pain. Which stimuli induce priming and what cellular mechanisms are employed remains incompletely understood. In adult male rats, we present the cytokine Oncostatin M (OSM), a member of the IL‐6 family, as an inducer of priming by a novel mechanism. We used a high content microscopy based approach to quantify the activation of endogenous PKA‐II and ERK of thousands sensory neurons in culture. Incubation with OSM increased and prolonged ERK activation by agents that increase cAMP production such as PGE2, forskolin, and cAMP analogs. These changes were specific to IB4/CaMKIIα positive neurons, required protein translation, and increased cAMP‐to‐ERK signaling. In both, control and OSM‐treated neurons, cAMP/ERK signaling involved RapGEF2 and PKA but not Epac. Similar enhancement of cAMP‐to‐ERK signaling could be induced by GDNF, which acts mostly on IB4/CaMKIIα‐positive neurons, but not by NGF, which acts mostly on IB4/CaMKIIα‐negative neurons. In vitro, OSM pretreatment rendered baseline TTX‐R currents ERK‐dependent and switched forskolin‐increased currents from partial to full ERK‐dependence in small/medium sized neurons. In summary, priming induced by OSM uses a novel mechanism to enhance and prolong coupling of cAMP/PKA to ERK1/2 signaling without changing the overall pathway structure. Abstract : Pain‐initiating signaling can be altered lastingly by a process called priming. Often, this has been attributed to switching of signaling pathways. Instead, we now find a novel priming substance, Oncostatin M, to increase signaling downstream of cAMP toward ERK while leaving the upstream signaling and the tested signaling pathway‐structure unchanged. Signaling from cAMP via EPAC toward ERK could not be detected. This translational dependent process was specific for IB4/CaMKIIα positive neurons and provides a novel mechanism of priming.